DESKRIPSI PENGGUNAAN MEDIA VIDEO YOUTUBE PADA PEMBELAJARAN TEMATIK KELAS V SEKOLAH DASAR NEGERI 61 KABUPATEN BENGKULU TENGAH - Elgi Tri Candra; Resnani Resnani; Nani Yuliantini (JURIDIKDAS, 2022)
This study aims to describe the steps to use and the quality of youtube video media in fifth grade Thematic learning at SDN 61 Central Bengkulu Regency. This study uses a descriptive method with a qualitative approach. The location of this research was carried out at SDN 61 Central Bengkulu Regency. The subjects of this study were teachers and students of  fifth grade SDN 61 Central Bengkulu Regency. The main instrument in this study was the researcher himself with the help of interview guidelines, observation sheets, and documentation. Data collection techniques used are interviews, observation, and documentation. The data obtained were then analyzed qualitatively based on the results of interviews, observations and documentation. From the results of data analysis, it shows that in the use of youtube video media by teachers at SDN 61 Central Bengkulu Regency, it is not yet fully guided by the learning steps using the correct youtube video media and in selecting youtube video media as learning media there are still youtube videos with good quality. not good and have not paid attention to the six aspects in the selection of youtube video media as learning media..